Violet in bloom a flower power book - Myracle, Lauren 1969- (Amulet Books, 2010)
Fifth-graders Katie-Rose, Violet, Milla, and Yasaman seem to have little in common except their flower-related names, but they nurture their new friendship through a social-networking site and a campaign to have healthier snacks served at school